Colorectal Carcinoma: Local Tumor Staging and Assessment of Lymph Node Metastasis by High-Resolution MR Imaging in Surgical Specimens. (2nd November 2009) - Yamada, Ichiro; Yoshino, Norio; Tetsumura, Akemi; Okabe, Satoshi; Enomoto, Masayuki; Sugihara, Kenichi; Kumagai, Jiro; Shibuya, Hitoshi
Abstract : Purpose . To assess the accuracy of high-resolution MR imaging as a means of evaluating mural invasion and lymph node metastasis by colorectal carcinoma in surgical specimens. Materials and Methods . High-resolution T1-weighted and T2-weighted MR images were obtained in 92 surgical specimens containing 96 colorectal carcinomas. Results . T2-weighted MR images clearly depicted the normal colorectal wall as consisting of seven layers. In 90 (94%) of the 96 carcinomas the depth of mural invasion depicted by MR imaging correlated well with the histopathologic stage. Nodal signal intensity on T2-weighted images (93%) and nodal border contour (93%) were more accurate than nodal size (89%) as indicators of lymph node metastasis, and MR imaging provided the highest accuracy (94%–96%) when they were combined. Conclusion . High-resolution MR imaging is a very accurate method for evaluating both mural invasion and lymph node metastasis by colorectal carcinoma in surgical specimens.